Disputas marítimas en el Caribe colombiano: la pesca de tortugas en el archipiélago de San Andrés y Providencia, 1910-1930 - Sharika Crawford (Historia Crítica, 2017)
There has been a long history of turtle hunting in the Greater Caribbean, especially in Colombian waters around the archipelago of San Andrés and Providence. This article is focused on Colombia’s efforts to affirm its national borders and to strengthen its control over its territorial waters, and on how the new regulations that these measures entail affect turtle hunters in the Caribbean Sea. Using travel stories, newspapers from Jamaica, Colombia and the United States, as well as diplomatic correspondence, interviews and secondary sources, this study analyzes the national and regional implications of these problems. This makes it possible to conclude that the islanders, in the company of Colombian officials, attempted to defend their insular territory and its maritime borders against both real and imaginary threats. Their efforts were aimed at restricting the extraction of marine resources within the country’s territorial waters, as part of the government’s interest in reinforcing the integrity of the Colombian nation-state in the Caribbean.